Adaptation Strategies by Muslim Convert : A Study on “Saudara Kita” in Sarawak Malaysia - Rasyidah, Abdullah; Samsiah, Jayos; Fatahyah, Yahya; Nur Fatihah, Abdullah Bandar; Nur Fatihat, Mat Yusoff (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2022)
The “Saudara Kita” is a term for the non-Malay Islamic community comprising various races and ethnicities in Sarawak, Malaysia. This term helps to identify the convert groups in Sarawak. This study was conducted to explore adaptation strategies used by Muslim converts in Sarawak. This qualitative research involved five participants who have converted to Islam for more than 5 years and reside in Sarawak. The data collection method used semi-structured interviews and data analyzed used thematic analysis. The research findings indicate five main themes arose for the adaptation strategies among Muslim converts, which are (1) exploring inner and outer challenges, (2) challenge adaptation strategies, (3) adaptation needs, (4) support system, and (5) exploring the role of counselors. The increase in the number of Islam converts in Sarawak each year requires exploration of challenge adaptions to plan developmental da’wah programs for Muslim converts, to enhance their Islamic faith. The objective of this program is to build a solid identity for Muslim converts so that they will be consistent in practicing the Islamic way of life. Governments in the Sarawak region can make programs in order to improve the knowledge, skills, and adaptation of converts in Sarawak. So that converts can have support from the government to carry out activities and worship in accordance with Islamic life.